SEJARAH PEMIKIRAN EKONOMI ISLAM IMAM AL MAQRIZI - Imron Fathurohman; Zumara Zumara; Hariyono Hariyono; Nour Khalid; Lutfi Maulana (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
This study will focus on Al Maqrizi's thoughts on money and inflation using a qualitative method with a literature study approach. Al-Maqrizi is in the second phase in the history of Islamic economics, a phase that is starting to show signs of slowing down innovative intellectual activities in the Islamic world. Meanwhile, Al-Maqrizi is an Islamic economic thinker who conducted a special study on money and inflation. Al-Maqrizi put forward some thoughts about money through a study of the history of the currency used by mankind. For Al-Maqrizi, the currency has a very important role in human life, both before and after the arrival of Islam, currency was used by mankind to determine the prices of various goods and labor costs. In the history and function of money, al-Maqrizi argued about the creation of currency with poor quality. According to him, the creation of currency with poor quality (bad money) will eliminate currency with good quality (good money). Furthermore, in al-Maqrizi's economic thought, he put forward the theory of inflation and he has classified inflation based on its causal factors into two things, namely inflation caused by natural factors and inflation caused by human error